Interpolations, Pseudographs, and the New Testament Epistles. - Barr, George K. (Literary & Linguistic Computing, 2002)
Scale-related patterns are found in all thirteen Pauline epistles. To test their distinctiveness, graphs of other texts, ancient and modern, comprising more than a million words, have been scrutinized; this survey has failed to detect any similar patterns. They may therefore be related to Pauline authorship. The longer passages claimed to be interpolations are tested against these scale-related patterns and are found to be essential parts of the original texts. Further scale-related patterns are found in 1 and 2 Peter (which received wisdom claims are pseudonymous writings) and in Hebrews. Consideration of these patterns and of the partnership of Paul and Silvanus in mission, leads to a possible solution to the problem of the hapaxes and throws light on the points of contact between the Paulines (including the Pastorals), 1 and 2 Peter, and Hebrews.